On the Determinants and Outcomes of Passion for Playing Pokémon Go - Orosz, Gábor; Zsila, Ágnes; Vallerand, Robert J.; Böthe, Beáta (Frontiers in Psychology, 2018)
In 2016, Pokémon Go became the most popular smartphone game. Despite the increasing popularity of this augmented reality game, to date, no studies have investigated passion for playing Pokémon Go. On the theoretical basis of the Dualistic Model of Passion, our goal was to investigate the associations between Pokémon Go playing motives, passion, and impulsivity. A total of 621 Pokémon Go players participated in the study (54.9% female; Mage = 22.6 years, SDage= 4.4). It was found that impulsivity was more strongly associated with obsessive passion (OP) than with harmonious passion (HP). HP was associated with adaptive motives (i.e., outdoor activity, social, recreation, and nostalgia), while OP was associated with less adaptive motives (i.e., fantasy, escape, boredom, competition, and coping). Therefore, in line with the Dualistic Model of Passion, HP and OP for playing Pokémon Go can predict an almost perfectly distinguished set of adaptive or maladaptive playing motives, and OP has a noteworthy relationship with impulsivity as a determinant.